DETERMINASI PENGUNGKAPAN TRANSAKSI PIHAK BERELASI BERDASARKAN PSAK NO. 7 TAHUN 2018 - Jessyka Tridewi Purba; Husnah Nur Laela Ermaya; Ayunita Ajengtiyas (Universitas Pakuan, 2020)
This study aims to examine the effect of audit committee, independent commissioner, institutional ownership, managerial ownership, earnings management to related party transaction disclosure. The samples used in this study are listed manufactured companies in 2016-2018. The total sample is 53 companies. The sampling technique that used is purposive sampling. The results of the study show that institutional ownership and managerial ownership significantly influence the disclosure of related party transactions. While the audit committee, independent commissioners and earnings management do not affect the disclosure of related party transactions. Companies are still more concerned about paying attention to financial information such as financial ratio analysis than non-financial information such as disclosure of related party transactions. Companies should pay more attention to non-financial which is useful for users of financial statements.